Pectin Extraction from Watermelon Rind for Application as a Coating on Apple Skin - Bumee, Ratri; Thiangphet, Patompong; Jamjang, Kwandaw; Phoomyai, Paklao (Journal of Science and Technology CRRU, 2024)
The objective of this research was to study the extraction of pectin from Watermelon rind species Sonya Plus for application as a coating on Apple skin species Fuji. The extraction factors with citric acid concentrations of 0.025, 0.050, 0.075 and 0.100 molar at temperature of 90 °C for 60 minute and the chemical properties of pectin were analyzed and pectin was evaluated. Dipping with various chemicals to Maintain Quality of fresh apple pulp in the period at 0, 6 and 12 days at 8 °C. It was found that, the highest concentration of citric acid at which pectin can be extracted is 0.100 molar yielding 0.82 g of pectin and 8.17 %. The results of chemical properties showed that, the moisture content, the galacturonic acid ontent, the methoxyl content and the %DE content were 6.77, 1.76, 53.18, 8.21 and 54.42 respectively. Pectin coating 2 % and dipping with chemical in the period at 12 days at 8 °C. This resulted in the lowest weight loss at 4.15 % and the lowest firmness loss at 7.27 N/mm.